Bilateral Mondor's disease in chikungunya virus infection. Issue 8 (10th August 2020) - Djebara, Sarah; Henckaerts, Liesbet; Vanbrabant, Peter
ABSTRACT: Chikungunya virus (CHIKV) is an arthropod-borne virus that is transmitted by Aedes mosquitoes, and its main features are high fever and (debilitating) arthritis. Infection with CHIKV, as well as other viruses, has been associated with hypercoagulable states and may be linked with the development of venous thrombosis. In fact, the development of deep venous thrombosis has been described in CHIKV infection. We present a case of superficial thrombophlebitis of the thoracic wall, known as Mondor's disease, associated with CHIKV infection. To our knowledge, this probable association has never been described before.